Grandparent support during childhood is associated with emotional wellbeing in emerging adulthood - Stephenson, Jane M.; Carstensen, Laura L. (Frontiers in Psychology, 2025)
BackgroundDue to longer life expectancies and age-related socioemotional strengths, grandparents are well-positioned to play roles that contribute positively to their grandchildren’s emotional development. Prior research shows that strong emotion regulation and social skills, as well as familial social support serves individuals well during emerging adulthood, a time when emotional wellbeing is challenged. Given this, and the fact that social and emotional skills are learned in early childhood, we reasoned that grandparental relationships in both early childhood and emerging adulthood may play an important role in the emotional wellbeing of their grandchildren in emerging adulthood.MethodsSurvey of 514 emerging adults (ages 18–29) who reported on their emotional wellbeing and family relationships. Support from grandparents during childhood was reported retrospectively along with reports of current support from grandparents. Analytical methods include multiple linear regression and moderated regression.ResultsSupport received from grandparents during early childhood was associated with greater emotional wellbeing in emerging adulthood. This association persisted even if grandparents had died before their grandchildren reached adulthood and was not moderated by relationship quality with parents or primary caregivers. Support from grandparents in emerging adulthood was also associated with emotional wellbeing during that time, and this association was complemented by support in childhood.DiscussionFindings highlight the importance of supportive grandparent relationships for grandchildren, pointing to the possibility that support during the developmental period when children are learning to regulate emotion and navigate social situations is especially protective of emotional wellbeing in emerging adulthood. This work underscores the importance of considering multiple generations and a life course perspective when examining how familial relationships are associated with wellbeing.